The Case Study On LSW International Sdn Bhd - Gatuma, Leonard Kiragu (2008)
LSW International ventured i786.pdfnto corporate training business in 2007. The core business of LSW International is corporate training workshops and conferences produced locally here in Malaysia with co-operation with local and foreign trainers from countries like Singapore, India, Australia and the USA.